Effect of acetaminophen exposure in oncorhynchus mykiss gills and liver: detoxification mechanisms, oxidative defence system and peroxidative damage - Ramos, A. S.
The increasing presence of pharmaceutical drugs in nature is cause of concern due to the occurrence of oxidative stress in non-target species. Acetaminophen is widely used in human medicine as an analgesic and antipyretic drug, and it is one of the most sold non-prescription drugs. The present study aimed to assess the toxic effects of acetaminophen (APAP) in Oncorhynchus mykiss following acute and chronic exposures in realistic levels. In order to evaluate the APAP effects in the rainbow trout, gills and liver were analyzed with biochemical biomarkers, such as catalase (CAT), total and selenium-dependent glutathione peroxidase (GPx), glutathione reductase (GRed) and glutathione-S-transferases (GSTs) activity and also lipid peroxidation levels (TBARS). The results obtained in all tests indicate that a significant response of oxidative stress was established, along with the increase of APAP concentrations. The establishment of an oxidative stress scenario occurred with the involvement of all tested biomarkers, sustaining a generalized set of pro-oxidative effects elicited by APAP. Additionally, the occurrence of oxidative damage strongly suggests the impairment of the antioxidant defense mechanism of O. mykiss. It is important to note that the occurrence of oxidative deleterious effects and peroxidative damages occurred for concentrations similar to those already reported for several freshwater ecosystems. The importance of these assumptions is further discussed under the scope of ecological relevance of the assessment of effects caused by pharmaceuticals in non-target organisms.